Classification and profiles of students based on their motivations concerning higher education - Habus-Korbar, Anja (Array, 2011)
Cluster analysis was used to create segments of high school graduates based on their motivations/opinions regarding their future education. Data for this study were collected using a questionnaire distributed to high school graduates following State Matura exam. The students were asked to evaluate the importance of 13 different reasons/causes for choosing the faculty selected as their first choice. The analysis yielded five meaningful clusters of students that differ not only in motivations but also in achievement on State Matura exams and in their preference regarding the scientific field of their future study.